Kinetic Method for Determination of Trace Amounts of Protein Based on its Inhibitive Effect on Potassium Periodate-(Dibromo-p-sulfonic acid arsenazo) Indicator Reaction - Zhai, Qing-Zhou; Yu, Hui; Hu, Wei-Hua; Zhu, Peng-Hui (Asian Journal of Chemistry, 2011)
A novel kinetic spectrophotometric method for the determination of protein is based on the inhibitive effect of bovine serum albumin (BSA) on the oxidation reaction of dibromo-psulfonic acid arsenazo (DBS-ASA) by potassium periodate in the medium of CH2ClCOOHCH3COONH4. The maximum absorption peak of BSA-(DBS-ASA)-KIO4 system is located at 530 nm. The absorbance difference ( DA) is well linearly related with the concentration of bovine serum albumin over the rage of 2.5-90.0 μg/mL of solution and fitted the equation: DA = 0.01091C + 0.0646 (C: μg/mL), with a correlation coefficient g = 0.9941. The detection limit of the method was 0.48 μg/mL. The method has been successfully used in the determination of the total content of protein in egg white and the relative standard deviation of 15 determinations were less than 5 %. The recovery of standard addition of the method was over the range of 100.1-101.2 %.